2021
DOI: 10.5430/ijfr.v12n5p10
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Aspects Hampering Informal Sector Tax Administration: Case of the Zimbabwe Revenue Authority

Abstract: The main focus of the study was to ascertain the potential of the informal sector to provide much-needed revenue for the government. It also focused on the challenges faced in informal sector revenue taxation and possible solutions thereof. The Zimbabwe revenue authority has maintained presumptive tax for the sector and subcontracting to the city of Harare for the collection of revenue from the informal sector. Despite all this, the industry still underperformed in terms of revenue raised. The study sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Using regression analysis, the study found that internally generated revenue had a positive effect on infrastructural development in the 3 senatorial districts based on the responses from the selected respondents. The result is consistent with the result obtained in the study of Otekunrin et al (2020) and Adegbie et al (2023).…”
Section: Empirical Reviewsupporting
confidence: 93%
See 2 more Smart Citations
“…Using regression analysis, the study found that internally generated revenue had a positive effect on infrastructural development in the 3 senatorial districts based on the responses from the selected respondents. The result is consistent with the result obtained in the study of Otekunrin et al (2020) and Adegbie et al (2023).…”
Section: Empirical Reviewsupporting
confidence: 93%
“…In the short run however, the impact of States/FCT and LGs IGR on Real GDP decreased to 0.08% and 0.03% respectively for a 1% rise in these IGRs, and Federal government IGR and total IGR showed no impact. The results were in tandem with prior studies that reported in similar significant results, the studies of Olabisi et al (2020); Otekunrin et al (2020) and Omodero et al (2018). On the contrary, some other studies reported an inverse result revealing negative effects (Etim & Daramola, 2020;Ironkwe & Ndah, 2016).…”
Section: Empirical Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Tax is one of the main sources of national fiscal revenue. Doing a good job in tax management is an effective way for the state to implement macrocontrol over enterprises [9,10]. The current situation is disturbed by many factors.…”
Section: Design Of Enterprise Tax Risk Intelligent Evaluation Methods...mentioning
confidence: 99%